Investigation of Leachate Treatment with Electrocoagulation and Optimization by Response Surface Methodology - Kabuk, Harun Akif; Ilhan, Fatih; Avsar, Yasar; Kurt, Ugur; Apaydin, Omer; Gonullu, Mustafa T. (WILEY-BLACKWELL, 2014)
This study examined the treatability of leachate with the electrocoagulation process and its optimization using the response surface method. The three-parameter optimization process and a 5-level, 6-replicate central composite design were included in the investigation on a set of 36 pieces created for the study. A second-order full polynomial approximation model was applied to evaluate the results of the optimization studies, which were performed for the removal of chemical oxygen demand, total suspended solids, total organic carbon, total Kjeldahl nitrogen, and NH3-N. When these parameters were compared, the appropriate working conditions obtained for current density and time were 20mAcm-2 and 60min, respectively, at pH 8. In this way, both pH adjustment and power costs were reduced.
Keywords: Landfill; Modeling; Solid waste; Wastewater treatment; WASTE-WATER TREATMENT; LANDFILL LEACHATE; ELECTRO-COAGULATION; ELECTROCHEMICAL TREATMENT; OPERATIONAL PARAMETERS; CHEMICAL-COAGULATION; DRINKING-WATER; CLEAN PROCESS; DYE SOLUTION; REMOVAL; Science & Technology - Other Topics; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources